The Role of Participatory Leadership in Solving School Principals Problems in Mafraq Governorate: A Field Study on the Principals of Public Schools in Mafraq Governorate/ Jordan - Khawaldah, Alaa Mahmoud (Journal of Educational and Psychological Sciences, 2020)
The study aimed at finding out the role of participatory leadership in solving problems school principals in Mafraq Governorate, and to achieve the goal of the study questionnaire was developed Consisting of (21) Item were confirmed validity and reliability, the study Society consisting of (158) Or principal, the study results showed that the role of participatory leadership in solving problems school principals in Mafraq Governorate, from the standpoint of the study sample was a fair degree, Or no differences in the study sample to the role of participatory leadership in solving problems school principals in Mafraq Governorate due to the gender and experience at the macro level of the instrument differences. In the light of those results, the study recommended the necessity of holding training courses to keep abreast of what is new in educational administration, and to identify leadership patterns, and how to apply the participatory style.